Erythropoietin increases expression and function of vascular CuZn-superoxide dismutase - d’Uscio, Livius V. (2010)
Previous studies have shown that treatment with erythropoietin (EPO) exerts vascular protective effects. The exact mechanisms responsible for these effects are not completely understood. In the present study we hypothesized that EPO stimulates expression and activity of CuZn-superoxide dismutase (SOD1) thus protecting vascular tissue from oxidative stress induced by excessive concentrations of superoxide anions. EPO treatment of wild type mice for two weeks (1000 U/kg, s.c., biweekly) significantly increased aortic expression of SOD1. This effect resulted in significant reduction of superoxide anion concentrations in aorta of treated mice. The ability of EPO to reduce vascular production of superoxide anions was abolished in SOD1-deficient mice. In mouse model of wire-induced injury of common carotid artery, treatment of wild-type mice with EPO prevented pathological remodeling whereas the vascular effect of EPO was absent in SOD1-deficient mice. Our findings demonstrate that treatment with EPO increases vascular expression of SOD1. This effect appears to be an important molecular mechanism underlying vascular protection by EPO.